2011
DOI: 10.1128/jcm.00854-11
|View full text |Cite
|
Sign up to set email alerts
|

Gestational and Fetal Outcomes in B19 Maternal Infection: a Problem of Diagnosis

Abstract: Parvovirus B19 infection during pregnancy is a potential hazard to the fetus because of the virus' ability to infect fetal erythroid precursor cells and fetal tissues. Fetal complications range from transitory fetal anemia and nonimmune fetal hydrops to miscarriage and intrauterine fetal death. In the present study, 72 pregnancies complicated by parvovirus B19 infection were followed up: fetal and neonatal specimens were investigated by serological and/or virological assays to detect fetal/congenital infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 23 publications
2
37
0
3
Order By: Relevance
“…Some case series also reported a high frequency of detection of B19 DNA in late intrauterine deaths [235][236][237], a finding not confirmed in other case series, that did not show such correlations and indicated that late intrauterine fetal death is a rare event [238]. Finally, the infected fetus may show presence of virus at birth [239,240]. Congenital infections have been sporadically associated with neonatal anemia or anomalies [241], while their possible consequences on the neurological development are currently investigated [242][243][244].…”
Section: Intrauterine Infection and Fetal Damagementioning
confidence: 96%
“…Some case series also reported a high frequency of detection of B19 DNA in late intrauterine deaths [235][236][237], a finding not confirmed in other case series, that did not show such correlations and indicated that late intrauterine fetal death is a rare event [238]. Finally, the infected fetus may show presence of virus at birth [239,240]. Congenital infections have been sporadically associated with neonatal anemia or anomalies [241], while their possible consequences on the neurological development are currently investigated [242][243][244].…”
Section: Intrauterine Infection and Fetal Damagementioning
confidence: 96%
“…It is well known that because of the pathophysiology of congenital CMV infection, several weeks may elapse before the appearance of sonographic findings of fetal infection . Previous studies on congenital parvovirus B19 infection have warned about maternal serum IgM levels possibly being low or undetectable at the time of clinically overt fetal hydrops, with substantial false negative results …”
Section: Discussionmentioning
confidence: 99%
“…The infection was confirmed via a polymerase chain reaction analysis of the amniotic fluid. IUETs were indicated in the cases with fetal hydrops (i.e., accumulation of fluid in at least two fetal compartments including ascites, pericardial effusion, pleural effusion, subcutaneous effusion, placental thickness, and hydramnios) or an MCA‐PSV greater than 1.5 to 1.55 multiple of the median (MoM) …”
Section: Methodsmentioning
confidence: 99%